2021
DOI: 10.1007/s12539-021-00461-4
|View full text |Cite
|
Sign up to set email alerts
|

Target-Based In Silico Screening for Phytoactive Compounds Targeting SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19), resulting from infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can cause severe and fatal pneumonia along with other life-threatening complications. The COVID-19 pandemic has taken a heavy toll on the healthcare system globally and has hit the economy hard in all affected countries. As a result, there is an unmet medical need for both the prevention and treatment of COVID-19 infection. Several herbal remedies have claimed to show promising cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Mapping based of binding hotspots data showed that PL pro presents only one organic probe cluster (site 1 ), whereas for the 3CL pro the results suggest the existence of four organic probe clusters (site 1 , site 2 , site 3 , and site 4 ). The position of the interaction sites on both receptors identified here (PL pro and 3CL pro ) did not differ from those previously reported (Abdizadeh et al 2022;Zhao et al 2022).…”
Section: Domain Analysis and Linker Prediction Of The Target Receptorssupporting
confidence: 53%
“…Mapping based of binding hotspots data showed that PL pro presents only one organic probe cluster (site 1 ), whereas for the 3CL pro the results suggest the existence of four organic probe clusters (site 1 , site 2 , site 3 , and site 4 ). The position of the interaction sites on both receptors identified here (PL pro and 3CL pro ) did not differ from those previously reported (Abdizadeh et al 2022;Zhao et al 2022).…”
Section: Domain Analysis and Linker Prediction Of The Target Receptorssupporting
confidence: 53%
“…Molavi et al repurposed 1760 FDA-approved drugs to Mpro and RdRp, and Rajpoot et al repurposed 291 drugs to Mpro and PLpro. More similar works include refs , , , , , , , , , , and .…”
Section: Methods and Approachesmentioning
confidence: 97%
“…Additionally, Zhao et al performed an in silico screening of a small herbal database to find potential direct-acting compounds against different non-structural SARS-CoV-2 targets. Accordingly, Amentoflavone with the highest affinity (-9.7 kcal.mol -1 )was highlighted as an nsp12 inhibitor [ 16 ]. Zhang et al translated the results of computational screening of 1906 approved drugs into in vitro assays.…”
mentioning
confidence: 99%